2015 IEEE/ACM 37th IEEE International Conference on Software Engineering 2015
DOI: 10.1109/icse.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Truth in Advertising: The Hidden Cost of Mobile Ads for Software Developers

Jiaping Gui,
Stuart Mcilroy,
Meiyappan Nagappan
et al.

Abstract: The "free app" distribution model has been extremely popular with end users and developers. Developers use mobile ads to generate revenue and cover the cost of developing these free apps. Although the apps are ostensibly free, they in fact do come with hidden costs. Our study of 21 real world Android apps shows that the use of ads leads to mobile apps that consume significantly more network data, have increased energy consumption, and require repeated changes to ad related code. We also found that complaints a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 27 publications
5
96
0
Order By: Relevance
“…For example, at the developers end, taint analysis [7] and instrumentation on binary or source form of apps are used to analyse whether they contain malicious code for security [15] and privacy [24] or whether certain features such as ads cause excessive energy and network consumptions for performance/usability quality [10]. At user's end, app store metadata such as app descriptions, popularity metrics such as number of downloads/installs, ratings, comments [6] are used for studying whether certain features are desired by certain cluster of users [23], or which features are offered by apps and which features are requested by users [11].…”
Section: Related Workmentioning
confidence: 99%
“…For example, at the developers end, taint analysis [7] and instrumentation on binary or source form of apps are used to analyse whether they contain malicious code for security [15] and privacy [24] or whether certain features such as ads cause excessive energy and network consumptions for performance/usability quality [10]. At user's end, app store metadata such as app descriptions, popularity metrics such as number of downloads/installs, ratings, comments [6] are used for studying whether certain features are desired by certain cluster of users [23], or which features are offered by apps and which features are requested by users [11].…”
Section: Related Workmentioning
confidence: 99%
“…Gui et al [32] performed a study to assess the hidden costs of mobile ads for developers. They selected 21 apps from the Google Play Store and evaluated the impact of ads, by comparing original versions against instrumented versions obtained via refactoring of the Google Mobile Ads API calls.…”
Section: Capra Et Almentioning
confidence: 99%
“…We can see that the application after the battery-aware transformation was able to decrease energy consumption by 5.86%. This result has to be seen relative to the potential power savings: removing ads completely yields 16% of average power savings [8], while our approach strikes the balance between the needs of mobile application developers and users. Furthermore, in lower power mode (i.e., low battery status, around 20%) even smaller savings in energy consumption can make a difference.…”
Section: Case Study: Energy Savingsmentioning
confidence: 99%
“…Impact of Advertisment on Mobile Applications: Work by Gui et al investigated the impact of ads on different resources, including energy consumption [8]. In a study considering similar aspects, Pathak et al examined where the energy is consumed in different apps, and found that thirdparty advertisement APIs is a large factor [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation